2021
DOI: 10.1097/mph.0000000000002161
|View full text |Cite
|
Sign up to set email alerts
|

Henoch-Schönlein Purpura With Scrotal Involvement: A Case Report and Literature Review

Abstract: Henoch-Schönlein purpura (HSP) is the most common vasculitis of childhood and affects the small blood vessels, leading to arthritis, abdominal pain, and renal involvement. However, scrotal involvement is a rare complication of HSP and scrotal pain. Swelling is the most frequent clinical presentation and can be easily confused with testicular torsion. If not treated in time, the scrotal inflammation will result in irreversible testicular necrosis. We report a 6-year-old male with HSP and scrotal involvement, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The external genitalia are implicated in every fifth male with Henoch–Schönlein syndrome [ 1 , 2 ]. Integrating and complementing the results of a recent review analyzing Henoch–Schönlein syndrome with scrotal involvement in 21 children [ 82 ], the discussion of this review will address the temporal relationship between the distinctive features of this vasculitis and the genital participation, the histopathology features, and the characteristics of penile and scrotal involvement, with emphasis on the ischemic testicular damage, and management.…”
Section: Discussionmentioning
confidence: 99%
“…The external genitalia are implicated in every fifth male with Henoch–Schönlein syndrome [ 1 , 2 ]. Integrating and complementing the results of a recent review analyzing Henoch–Schönlein syndrome with scrotal involvement in 21 children [ 82 ], the discussion of this review will address the temporal relationship between the distinctive features of this vasculitis and the genital participation, the histopathology features, and the characteristics of penile and scrotal involvement, with emphasis on the ischemic testicular damage, and management.…”
Section: Discussionmentioning
confidence: 99%
“…Acute scrotum, ureteritis, bladder wall hematoma, hemorrhagic spermatic cord, thrombosis of spermatic veins, and epididymo-orchitis may develop as extrarenal genitourinary manifestations in IgAV patients. [8] The first case of IgAV male genital involvement was published in 1960 and it was shown that 2-38% of IgAV patients may develop scrotal involvement. [9,10] In 2021, Ma et al reviewed IgAV patients with scrotal involvement in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In 2021, Ma et al reviewed IgAV patients with scrotal involvement in the literature. [8] Between 1986 and 2020, 21 case reports of children with IgAV showed describing scrotal involvement. The mean age of onset of IgAV with scrotal involvement was 5.69±2.12 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Acute scrotum associated with HSP is treated conservatively. 7 Because testicular torsion may occur and requires…”
mentioning
confidence: 99%